2012
DOI: 10.1371/journal.pone.0037797
|View full text |Cite
|
Sign up to set email alerts
|

CCL18 in a Multiplex Urine-Based Assay for the Detection of Bladder Cancer

Abstract: The early detection of bladder cancer (BCa) is pivotal for successful patient treatment and management. Through genomic and proteomic studies, we have identified a number of bladder cancer-associated biomarkers that have potential clinical utility. In a case-control study, we examined voided urines from 127 subjects: 64 tumor-bearing subjects and 63 controls. The urine concentrations of the following proteins were assessed by enzyme-linked immunosorbent assay (ELISA); C-C motif chemokine 18 (CCL18), Plasminoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 27 publications
(30 reference statements)
2
73
0
1
Order By: Relevance
“…CCL-18 acts through autocrine and paracrine signaling, and participates in immunologic and inflammatory processes (Urquidi et al, 2012). Previous studies have shown that CCL-18 also has the ability affect tumorigenesis, and can affect the grade and prognosis of ovarian, colon, and gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CCL-18 acts through autocrine and paracrine signaling, and participates in immunologic and inflammatory processes (Urquidi et al, 2012). Previous studies have shown that CCL-18 also has the ability affect tumorigenesis, and can affect the grade and prognosis of ovarian, colon, and gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapy acts on the genetic pathways responsible for BC, 4 which is regarded as the nextgeneration therapy for the disease with the help of genomic and proteomic techniques. 3,9 MicroRNA (miR) is a short non-coding RNA sequence which plays an important role in adjusting gene expressions. It binds to the 3′ untranslated region (UTR) of target messenger RNAs (mRNAs) and affects the corresponding transcription process.…”
Section: Introductionmentioning
confidence: 99%
“…Using commercial ELISA assay kits directed at the biomarker panel, we performed three independent experiments. First, we analyzed voided urines from 127 subjects (64 with BCa and 63 controls) and confirmed that 10 of the 14 biomarkers were significantly altered in BCa compared to controls [13][14][15][16]. Next, we reported the validation of the 10-biomarker diagnostic panel (IL8, MMP9, MMP10, SERPINA1, VEGFA, ANG, CA9, APOE, SDC1 and SERPINE1) in a large cohort of patients (n = 308; 102 BCa and 206 controls) including controls with diverse urologic conditions (e.g., urolithiasis, moderate-severe voiding symptoms, urinary tract infection and hematuria) [17].…”
Section: Open Accessmentioning
confidence: 72%
“…We have reported the derivation and the validation of the urinary 10-biomarker BCa diagnostic signature in a number of studies with a total of over 800 subjects [13][14][15][16][17][18]. Recent work from our laboratory using quantitative immunohistochemical staining techniques for the detection of the signature proteins has shown a strong association of expression and malignancy in human bladder tumor tissues [27].…”
Section: Discussionmentioning
confidence: 99%